(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Fitmawati, Roza RM, Emrizal, Juliantari E, Almurdani M. 2022. The potency of wild mango Mangifera magnifica as a new source of antidiabetic agents with concurrent antioxidant activity. Biodiversitas 23: 5159-5164. Diabetes mellitus has entered the top 10 causes of death, following a significant percentage increase of 70% since 2000. Researchers have been working on a new practical design of ?-glucosidase inhibitor from plant resources that can be used as a therapeutic agent for diabetes mellitus. By inhibiting ?-glucosidase, the digestion of carbohydrates slows down, which helps prevent hyperglycemia. In our preliminary study, M. magnifica is a neglected wild mango shown to have high levels of antioxidant activity. We conducted a study on the wild mango species M. magnifica as an ?-glucosidase enzyme inhibitor. Antioxidant activities were carried out by the method of radical reduction 1,1-diphenyl-2-picrylhydrazyl (DPPH). Total phenolic content (TPC) was calculated by the Folin-Ciocalteu method and total flavonoid content (TFC) was calculated by colorimetric method. The antidiabetic activity was carried out by in vitro ?-glucosidase biochemical test. The methanol extract and ethyl acetate fraction have high antioxidant activity and the strongest inhibitory ?-glucosidase activity. M. magnifica leaves are a new source of antihyperglycemic agents with concurrent antioxidant activity. The research results will provide new information to support conservation efforts whose status is already rare while maintaining and improving the quality of value and diversity.